Shaking Heritage Museum Collections between Seismic Vulnerability and Museum Design - CERRI, GIADA (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Any moment the earth can shake, but we do not know when or where. If it happens, our Heritage might be in danger. Shaking Heritage addresses the topic of the seismic vulnerability of museum collections. It develops a way to assess the seismic risks for movable Heritage, proposing a synthetic method to rate the vulnerable settings. It discusses the necessity of integrating museography and anti-seismic solutions for museums and exhibitions, and studies exhibit solutions that would improve the seismic safety of collections and setups. It stresses the necessity of constructing shared guidelines and policies for the safety of the movable Heritage. Shaking Heritage is a step forward in acknowledging the importance of the anti-seismic culture among museum institutions and researchers.